Evaluasi Aplikasi Kompos Blok pada Tumbuhan Cemara Laut (Casuarina equisetifolia L.) di Lahan Marginal - Khoryfatul Munawaroh; Yesika Gultom; Rio Ardiansyah Murda (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Marginal land is land that has various limiting factors that inhibit plant growth, both in terms of its physical and chemical aspects. This condition is generally formed due to anthropogenic activities that significantly change soil characteristics. One example occurred at the Itera Botanical Gardens, specifically during the construction of the Sumatra Embung (reservoir). The Sumatra Embung construction process caused excavated soil to be stockpiled in the surrounding area, resulting in changes in the soil profile and physical and chemical properties. Soil quality degradation is reflected in the suppressed growth performance of plants around the reservoir area. Species of plants have been planted at the location with different initial treatments. Therefore, this study aims to evaluate the growth rate of Casuarina equisetifolia treated with block compost four months after planting in the field. This study used a factorial completely randomized design (CRD) with a split-plot design. Data analysis used Minitab 19 software, followed by the Least Significant Difference (LSD) test at the 5% level. Observed parameters included plant height, stem diameter, and canopy width. The LSD test results showed that the K2 treatment (without mycorrhiza + block compost formula 2) provided the best growth response across all observed parameters. Plant heiht K2 increased by 111.33 cm, diameter by 1 cm, and canopy width by 75.9 cm. These results confirm that block compost has slow-release properties, as evidenced by consistent plant growth trends as in previous studies. Meanwhile, the application of mycorrhiza did not show a significant increase in growth compared to the treatment without mycorrhiza.